Greece’s Breaking Away from the Public Monopoly on Higher Education - Vasilopoulos, Andreas; Dourgkounas, George (International Higher Education, 2025)
Andreas Vasilopoulos is assistant professor at the University of Patras, Greece. E-mail: andreasv@upatras.gr.